Land Utilization as Green Open Space and City Park as Public Space in Lima Puluh District, Batu Bara Regency, North Sumatra Province - Tavy Juanda; Abdi Sugiarto; Cut Nuraini (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This study aims to examine Land Utilization as Green Open Space and City Park as Public Space in Lima PuluhDistrict, Batu Bara Regency, North Sumatra Province. This study uses a qualitative descriptive method thatemphasizes on the aspect of natural object conditions. Data collection techniques are the means used to obtainthe data and information needed to achieve research objectives. In this case, the researcher conducted severaldata analysis techniques, data reduction, data presentation and preliminary conclusion. The results of theresearch on land use in Limapuluh District have 2 areas, namely the built land area and the unbuilt land area.The land use area in Limapuluh District is 99.1 hectares which is dominated by unbuilt land areas. To be able tomeet the needs of public RTH land in each sub-district in Limapuluh District, at least 1 public RTH in 1 sub-districtand optimization of existing vacant lands to be converted into public RTH, especially on vacant land in subdistricts that have little availability of vacant land. Meanwhile, the suggestion for the community to takeadvantage of vacant land by creating a garden in the yard of the house and maintaining and maintaining publicRTH facilities that have been built by the government so as to realize a high and comfortable quality of livingenvironment.